Etnomedisin Penyakit Dalam pada Suku Dayak Tabun di Desa Sungai Areh Kecamatan Ketungau Tengah Kabupaten Sintang - Riza Linda, Tri Wildayati, Irwan Lovadi, (Universitas Tanjungpura, 2015)
Ethnomedicine is a branch of medical anthropology which discusses the origin of diseases, their causes and treatment in accordance with a particular community group. This research conducted to find out the types of plants utilized as medicine for internal diseases by the Tabun Dayak in Sungai Areh Village, Sub-District of Central Ketungau. Sintang Regency, the benefits and the ways of processing. The research was carried out from March until June 2015 in Sungai Areh Village. The respondents were selected through the snowball method, while information about traditional medicine was obtained from interviews with the respondents. The data were analyzed using both qualitative and quantitative analysis. The qualitative analysis was conducted to find out the types of plants, parts that were used and the processing methods. The quantitative analysis used the Frequency of Citation (FIC) and the Informant Agreement Ratio (IAR). The research found 28 species belonging to the 22 families. The most widely used family was theZingiberaceae which consisted of 4 types of plants. The most widely used part of the plant was the root. The most common ways of processing the plants were by boiling and grindingthem first. The category of plant utilization was divided into 6,i.e.to treat cancer, excretory system, digestive system, respiratory system, reproductive system, and circulatory system. The highest citation frequency in this research was 92.87%;the highest score of the Informant Agreement Ratio (IAR) was in the category of the excretory system disease, i.e. 0.952.